PWE-053 Multicentre European Study of Double Balloon Enteroscopy in Patients with Cardiovascular Disease: A Relationship Without Heartbreak?. (17th August 2016) - Ching, H-L; Branchi, F; Yung, DE; Koulaouzidis, A; Plevris, J; Elli, L; Sanders, DS; Sidhu, R
Abstract : Introduction: Double balloon enteroscopy (DBE) is a relatively invasive and lengthy procedure necessitating careful consideration of patients' comorbidities. We aim to assess the safety of DBE in patients with cardiovascular disease (CVD). Methods: Between June 2006 and January 2016, 568 consecutive patients undergoing DBE were reviewed across 3 teaching hospitals in the UK and Italy. Demographic and clinical data were collected and patients were categorised by age (elderly: ≥70 years and young: <70 years) and the presence or absence of CVD. Comparisons were made of diagnostic and therapeutic yields and complications rates. Results: CVD was present in 185 patients (mean age 70±9.7, 51% male) who underwent DBE for iron deficiency anaemia (54%) overt gastrointestinal bleeding (25%), suspected Crohn's disease (10%), small bowel strictures (6%) and suspected coeliac disease complications (4%). CVD (elderly vs young) included ischaemic heart disease (59% vs 68%, p = 0.2), valve replacement (23% vs 16%, p = 0.3), atrial fibrillation (31% vs 11%, p < 0.05 ) and congestive cardiac failure (21% vs 8.5%, p < 0.05 ). The 2 groups (elderly vs young) had similar propofol requirements (1320 mg vs 999 mg, p = 0.5), but midazolam (4 mg vs 5.5 mg, p < 0.05 ) and fentanyl (36.5 mcg vs 75 mcg, p < 0.05 ) use was less in the elderly. The most common abnormalities (elderly vs young) were ulcers (5.5% vs 10%, p = 0.4), strictures (3% vs 3%, p = 1.0), tumours (2% vs 7%, p = 0.2) and angioectasias (43% vs 27%, p < 0.05 ). Diagnostic yield (67% vs 64%, p = 0.8) and complication rates (5.5% vs 2%, p = 0.3) were comparable. However, therapeutic yield was higher in the elderly (50.5% vs 33%, p < 0.05 ). All CVD patients were compared to 383 patients without CVD (mean age 50±14.1, 44% male). Diagnostic yield was higher in those with CVD compared to those without (65% vs 50%, p < 0.05), as was therapeutic yield (42% vs 17%, p < 0.05). Irrespective of age, angioectasias were commoner in patients with CVD compared to those without (34.6% vs. 8.4%, p < 0.05). The difference seen in complications between both groups was not significant (2.7% vs 0.8%, p = 0.12). Complications seen in the CVD group included 2 cases of systemic infections, 2 cases of respiratory compromise and 1 case of myocardial infarction. Conclusion: We report the first multicentre study attesting the safety of patients with CVD undergoing DBE. Moreover, patients with CVD have higher diagnostic and therapeutic yield at DBE and thus with careful selection, these patients are most likely to benefit from the procedure. Disclosure of Interest: None Declared